Women Empowerment: A Comparison of Socio-Economic Perspectives with Political Aspects - Mehmood, Bushra; Khan, Abdul Jalil; Ahmad, Hafiz Rizwan (Pakistan Journal of Humanities and Social Sciences, 2024)
This study aims to investigates the social, economic and some political determinants of women empowerment by determining whether economic and social factors are more important compared to the political factors or not. The comparison between 34-developed and 34-developing countries has been made by constructing a weighted index of women empowerment by using annual data ranging from 1990 to 2023 based on the social and economic spheres of the women life. The political aspects are employed by using women political empowerment index already developed by V-Dem. The study evaluates the capability approach through panel data fixed effects models. This approach conceptualizes women empowerment by focusing social and economic dimensions of the women life mainly. Panel data analysis has been performed based on cross section fixed effect models and generalized least square regression with ARMA components to deal with autocorrelation. The findings suggest that developing countries need to advance the socio-economic factors to empower their women population such as increased educational access, raising the level of life expectancy and provide opportunities for political role whereas developed countries should focus on expansion in economic opportunities and health facilities for women to ensure the women empowerment effectively. Hence the set of policies needed in case of developing countries should focus more on social empowerment whereas developed countries more on economic empowerment.